MOLECULAR CLONING, EXPRESSION AND FUNCTIONAL INTERACTION OF p48 SUBUNIT OF CHICKEN CHROMATIN ASSEMBLY FACTOR 1 WITH HISTONE DEACETYLASE 2 AND HISTONE ACETYLTRANSFERASE 1 - Ahyar Ahmad (Indonesian Journal of Chemistry, 2012)
We cloned and sequenced cDNA encoding p48 subunit of the chicken CAF-1, chCAF-1p48, and histone acetyltransferase-1, chHAT-1 from chicken DT40 cell lines. We showed that the p48 subunit of CAF-1 tightly binds to two regions of chicken histone deacetylase 2, chHDAC-2, located between amino acid residues 82-180 and 245-314, respectively. We also established that two N-terminal, two C-terminal, or one N-terminal and one C-terminal WD repeat motif of chCAF-1p48 are required for this interaction. The GST pulldown assay, involving truncated and missense mutants of chCAF-1p48, revealed not only that a region containing the seventh WD dipeptide motif of chCAF-1p48, comprising amino acids 376-405, binds to chHAT-1 in vitro, but also that mutation of the motif has no influence on the in vitro interaction. We also established that the region, which is located between amino acids 380-408 of chHAT-1 and contains a leucine zipper motif, is required for its in vitro interaction with chCAF-1p48. Mutation on each of four Leu residues in the leucine zipper motif of chHAT-1 causes the disappearance of the interaction with chCAF-1p48. These results should be useful information for understanding the participation of chCAF-1p48 protein as histones chaperone in DNA-utilizing processes, such as replication, recombination, repair and gene expression in DT40 chicken B cell.